INVESTIGATIONS OF BURIED STRUCTURE ENHANCED BY GEOSYNTHETIC PRODUCTS: A REVIEW - RAHIM, MAYSAM ABDUL WAHHAB; AL-BUSALTAN, SHAKIR; AL-NADDAF , MAHDI (Journal of Duhok University, 2023)
particularly when new roadways or bridges are constructed over these vital infrastructures. Various accidents or natural disasters may damage them. As a result of the pipe’s wall full force and non-uniform load, shallowly buried pipes exposed to surface loads experience greater bending strains and are susceptible to failure. The reduced confinement of the soil backfill exacerbates these issues as well. Different geosynthetic products have demonstrated that they can be utilized to protect buried structures. To better comprehend the effects of different geosynthetic products on soil-buried structure interaction, this research performed a review investigation series for experimental, numerical, and field tests under repeated loads to evaluate the behavior of buried structures, soil responses, and geosynthetic mechanisms. A recap of previous study results and a discussion of the subject’s research gaps are offered. Based on previous research, it is intelligible that geosynthetics are becoming a viable and sustainable approach for ground reinforcement. In addition, the findings demonstrated many parameters affect the degree of protection by geosynthetics, including the geogrid or geocell width, geogrid or geocell installation depth, geofoam height, the effectiveness of granular backfill stiffness and increased embedment depth.